The Development of Teaching Materials in Addictives Subtances and Psychotropic on Problem Based Learning and Conservation in MA - Ramadhani, Kharisma Riski; Lisdiana, Lisdiana; Pukan, Krispinus Kedati (Journal of Biology Education, 2021)
Development of teaching materials is an activity that can broaden and deepen the learning materials so that more applicable. Excess use of materials is compiled detailed material tailored to the student's ability level and learning objectives. This research aims to develop teaching materials addictive and psychotropic substances based Problem Based Learning and conservation in MA with krieria effective. This type of research Research and Development (R & D) to study measures following the 10 steps according Sugiyono research. Readability test is done with the subject 36 students and the implementation of teaching materials made on the subject of 145 students.The results showed a score validation by expert media teaching materials and the material is very valid. The results of students' cognitive learning consists of classical completeness amounted to 80.56% of students received grades above KKM and N-gain of 97.2% of students obtain N-gain in the criteria for moderate to high. The result of the strengthening score caring attitude within the criteria very well(89.14%). Based on the results, it can be concluded that the teaching materials addictive and psychotropic substances based on Problem Based Learning and conservation are developed effectively used for student learning MA.